Double Fertilization Embryo and Endosperm Development in Flowering Plants - Raghavan, Val.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
"Double Fertilization" provides a comprehensive overview of all aspects of this central event in the reproduction and development of flowering plants. Written by Val Raghavan, The Ohio State University, an acknowledged expert in plant developmental biology, the book vividly describes the molecular and cellular steps of the unique and complex fertilization process that culminates in the formation of embryo and endosperm, focusing on the latest results from the model plant Arabidopsis. The text is complemented by excellent illustrations, including 16 color plates. Since embryo and endosperm constitute the edible parts of many seeds and grains widely used in human and animal nutrition, an understanding of the fertilization process has great relevance for genetic engineering aimed at improving the nutritional quality of crop plants. This book is ideally suited to researchers and graduate students seeking a coherent view of current perspectives on embryogenesis and endosperm development in flowering plants.
Double Fertilization $1 (BA Defining Feature of Flowering Plants -- Establishment of the Embryo Body Plan $1 (BA Reassessment of Cell Lineage and Cell Fate -- Pattern Formation in Embryos $1 (BInterpretation of Positional Information -- Life and Times of the Suspensor $1 (BCell Signaling between the Embryo and Suspensor -- Genetic and Molecular Control of Embryogenesis $1 (BRole of Nonzygotic and Zygotic Genes -- Maturation and Dormancy $1 (BSurvival Strategies of the Embryo -- Developmental and Functional Biology of the Endosperm $1 (BA Medley of Cellular Interactions -- Genetics and Molecular Biology of the Endosperm $1 (BA Tale of Two Model Systems -- Non-zygotic Embryo Development $1 (BEmbryogenesis without Sex.s
Keywords: Life sciences; Nutrition; Developmental biology; Plant science; Botany; Plant anatomy; Plant development; Plant genetics; Life Sciences; Plant Genetics & Genomics; Plant Anatomy/Development.; Developmental Biology; Plant Sciences; Nutrition; Electronic books